Spectrophotometric Determination of Amoxicillin, Ampicillin, Cefalexin and Cefadroxil in Pharmaceutical Formulations, Biological Fluids and Spiked Water Samples. Issue 3 (4th May 2019) - Sharma, D.K.; Sood, Sumita; Raj, Pushap
Abstract: Amoxicillin, ampicillin, cefalexin and cefadroxil are the most extensively used beta-lactam antibiotics due to their broad spectrum of action and low cost. The quality of the pharmaceutical formulations of these drugs being marketed needs to be ensured to achieve a better remedial effect and a lower toxicity. The widespread exploitation of antibiotics sometimes leads to their presence in residues in body fluids and water bodies, which is potentially toxic and dangerous for human health. Thus, the determination of these drug compounds in pharmaceutical formulations, biological fluids and in water samples is of great importance and scope. Owing to the inherent ease and simplicity and sensitivity of spectrophotometric methods, the reactions of above drug compounds with carbon disulphide and copper(I) perchlorate in the presence of pyridine to form acrylonitrile extractable yellow coloured copper(I) drug dithiocarbamate complexes has been investigated for the spectrophotometric determination of these drugs. The analysis is accomplished by measuring the intensity of yellow extract at 450, 378, 380 and 430 nm for amoxicillin, ampicillin, cefalexin and cefadroxil respectively against a reagent blank. Under the optimized condition calibration graphs were linear in the ranges of 1.68-167.78, 1.61-161.38, 1.39-138.96 and 1.45-145.36 μg/mL with the detection limit (3.3 σ / s) of 1.24, 1.19, 1.07 and 1.13 μg/mL respectively. The high recoveries of the listed drugs by the proposed method from respective pharmaceutical formulations (98.80-100.30 %), simulated biological fluids (98.46-100.21 %) and spiked water samples (98.32-99.66 %) with RSDs in the ranges 0.15-1.11 % indicate good accuracy and precision of the method.